2021
DOI: 10.3390/diagnostics11071261
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Bochdalek Hernia during Pregnancy: A Systematic Review of Case Reports

Abstract: Background: Since the first report of a diaphragmatic hernia from Ambroise Paré’s necropsy in 1610, the Bochdalek hernia (BH) of the congenital diaphragmatic hernia (CDH) has been the most common types with high morbidity and mortality in the neonatal period. Due to the nature of the disease, CDH associated with pregnancy is too infrequent to warrant reporting in the literature. Mortality of obstruction or strangulation is mostly due to failure to diagnose symptoms early. Data sources and study selection: A sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 55 publications
2
18
3
Order By: Relevance
“…(Symptomatic) DH in pregnancy is exceedingly rare, with the collection of 43 maternal Bochdalek hernia cases from 1941 to 2020[ 5 ]. We collected 158 cases, although an additional number was unavailable or with incomplete data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Symptomatic) DH in pregnancy is exceedingly rare, with the collection of 43 maternal Bochdalek hernia cases from 1941 to 2020[ 5 ]. We collected 158 cases, although an additional number was unavailable or with incomplete data.…”
Section: Discussionmentioning
confidence: 99%
“…Although a recent systematic review of 43 Bochdalek hernias was published[ 5 ], there are still no recommendations and guidelines for this condition during pregnancy. We present the largest systematic review of DH in pregnancy (158 cases) over more than 100 years and propose a treatment algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…This could range from engaging in physically demanding labor, or something casual like playing a game of tug-of-war. 26 Although a recent review has shown a poor correlation of diaphragmatic hernia and increased intra-abdominal pressure seen in pregnancy, labor, and delivery, 27 it was always believed they contribute to the non-traumatic incidence of CDH. 28,29 Even something as trivial as sneezing, coughing or ingestion of a large meal have been reported to cause a diaphragmatic hernia.…”
Section: Discussionmentioning
confidence: 99%
“…First, in 2021, Choil and my co-worker reported a systematic review of congenital Bochdalek hernia during pregnancy. 1 …”
Section: Dear Editormentioning
confidence: 99%